The Pan-Cancer Landscape of Coamplification of the Tyrosine Kinases KIT, KDR, and PDGFRA - (:unkn) unknown (WILEY, 2020)
Purpose Amplifications of receptor tyrosine kinases (RTKS) are therapeutic targets in multiple tumor types (e.g. HER2 in breast cancer), and amplification of the chromosome 4 segment harboring the three RTKs KIT, PDGFRA, and KDR (4q12amp) may be similarly targetable. The presence of 4q12amp has been sporadically reported in small tumor specific series but a large-scale analysis is lacking. We assess the pan-cancer landscape of 4q12amp and provide early clinical support for the feasibility of targeting this amplicon. Experimental Design Tumor specimens from 132,872 patients with advanced cancer were assayed with hybrid capture based comprehensive genomic profiling which assays 186-315 genes for all classes of genomic alterations, including amplifications. Baseline demographic data were abstracted, and presence of 4q12amp was defined as 6 or more copies of KIT/KDR/PDGFRA. Concurrent alterations and treatment outcomes with matched therapies were explored in a subset of cases. Results Overall 0.65% of cases harbored 4q12amp at a median copy number of 10 (range 6-344). Among cancers with >100 cases in this series, glioblastomas, angiosarcomas, and osteosarcomas were enriched for 4q12amp at 4.7%, 4.8%, and 6.4%, respectively (all p < 0.001), giving an overall sarcoma (n = 6,885) incidence of 1.9%. Among 99 pulmonary adenocarcinoma cases harboring 4q12amp, 50 (50%) lacked any other known driver of NSLCC. Four index cases plus a previously reported case on treatment with empirical TKIs monotherapy had stable disease on average exceeding 20 months. Conclusion We define 4q12amp as a significant event across the pan-cancer landscape, comparable to known pan-cancer targets such as NTRK and microsatellite instability, with notable enrichment in several cancers such as osteosarcoma where standard treatment is limited. The responses to available TKIs observed in index cases strongly suggest 4q12amp is a druggable oncogenic target across cancers that warrants a focused drug development strategy. Implications for Practice Coamplification of the receptor tyrosine kinases (rtks) KIT/KDR/PDGFRA (4q12amp) is present broadly across cancers (0.65%), with enrichment in osteosarcoma and gliomas. Evidence for this amplicon having an oncogenic role is the mutual exclusivity of 4q12amp to other known drivers in 50% of pulmonary adenocarcinoma cases. Furthermore, preliminary clinical evidence for driver status comes from four index cases of patients empirically treated with commercially available tyrosine kinase inhibitors with activity against KIT/KDR/PDGFRA who had stable disease for 20 months on average. The sum of these lines of evidence suggests further clinical and preclinical investigation of 4q12amp is warranted as the possible basis for a pan-cancer drug development strategy.
Keywords: amplification; tyrosine kinase inhibitor; KIT; PDGFRA; genomic profiling; sarcoma; CHROMOSOMAL SEGMENT 4Q12; PHASE-II; PRECISION ONCOLOGY; AXITINIB AG-013736; OPEN-LABEL; AMPLIFICATION; MULTICENTER; IMATINIB; BENEFIT; TRIAL